Changes in Vasodilator-Stimulated Phosphoprotein Phosphorylation, Profilin-1, and Cofilin-1 in Accreta and Protection by DHA. (June 2019) - Ali, Mehboob; Rogers, Lynette K.; Heyob, Kathryn M.; Buhimschi, Catalin S.; Buhimschi, Irina A.
Accreta and gestational trophoblastic disease (ie, choriocarcinoma) are placental pathologies characterized by hyperproliferative and invasive trophoblasts. Cellular proliferation, migration, and invasion are heavily controlled by actin-binding protein (ABP)-mediated actin dynamics. The ABP vasodilator-stimulated phosphoprotein (VASP) carries key regulatory role. Profilin-1, cofilin-1, and VASP phosphorylated at Ser157 (pVASP-S157) and Ser239 (pVASP-S239) are ABPs that regulate actin polymerization and stabilization and facilitate cell metastases. Docosahexaenoic acid (DHA) inhibits cancer cell migration and proliferation. We hypothesized that analogous to malignant cells, ABPs regulate these processes in extravillous trophoblasts (EVTs), which exhibit aberrant expression in placenta accreta. Placental–myometrial junction biopsies of histologically confirmed placenta accreta had significantly increased immunostaining levels of cofilin-1, VASP, pVASP-S239, and F-actin. Treatment of choriocarcinoma-derived trophoblast (BeWo) cells with DHA (30 µM) for 24 hours significantly suppressed proliferation, migration, and pVASP-S239 levels and altered protein profiles consistent with increased apoptosis. We concluded that in accreta changes in the ABP expression profile were a response to restore homeostasis by counteracting the hyperproliferative and invasive phenotype of the EVT. The observed association between VASP phosphorylation, apoptosis, and trophoblast proliferation and migration suggest that DHA may offer a therapeutic solution for conditions where EVT is hyperinvasive.